IMPLEMENTASI GOOD CORPORATE GOVERNANCE (GCG) DALAM MENINGKATKAN KINERJA KEUANGAN PADA PT. PERUSAHAAN GAS NEGARA (PGN) Tbk. MEDAN - Reviwya Gesti Paningrum; Ali Usman (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2016)
This study aims to determine whether implementation of good corporate governance can increase financial kineja at PT. National gas Company. The population in this study are all implementation of good corporate governance in improving financial performance at PT. Perusahaan Gas Negara, samples are Implemnetasi Good Corporate Governance in improving financial performance. Perusahaan Gas Negara Tbk. 2012-2014 year, type of data used in this study using quantitative and qualitative data type, source data used in this research is secondary data, the data collection techniques in this study using interview techniques and Documentation, Technical Analysis of the data used is Descriptive Analysis , Research Shows that PT. National Gas Company has implemented good corporate governance Good with achieving value 92.14%, but in terms of financial performance as measured by the ratio of Return On Equity (ROE) impairment in current year profit amounted to 17.43%.